Non Excusable Delays in Construction Industry: A Causal Study - Khahro, S. H.; Memon, Z. A. (Engineering, Technology & Applied Science Research, 2018)
Delays are one of the major problems construction industry faces. Delays can lead to many negative effects such as arbitration between owners and contractors, increased cost, loss of productivity and revenue, and contract termination. Various studies have been carried out to highlight the general causes of delays and suggest possible remedial measures to minimize the effect of delays on a project. This study aims to highlight the critical factors with specific reference to non-excusable delays (NEDs) only. It also suggests possible remedial measures to minimize the effects of contractor-oriented NEDs which is a significant type of delays in the construction industry. A qualitative study has been conducted for this research. Data have been collected by the use of a set of questionnaires on numerous construction project stakeholders. Relative importance index (RII) has been used for prioritizing the factors. Results show that slow material mobilization, subcontractor unreliability and shortage of labor and materials are the most critical NED causes. This paper aims to provide a prerequisite knowledge to practitioners to make a more informed decision in managing NED.